Glutaredoxin 2 Reduces Asthma-Like Acute Airway Inflammation in Mice - Hanschmann, Eva-Maria; Berndt, Carsten; Hecker, Christina; Garn, Holger; Bertrams, W.; Lillig, Christopher H.; Hudemann, Christoph (Frontiers in Immunology, 2020)
Endogenous redox systems not only counteract oxidative damage induced by high levels of hydroxyl radicals (OH·) under pathological conditions, but also shape redox signaling as a key player in the regulation of physiological processes by hydrogen peroxide (H2O2). Thioredoxins (Trx), glutaredoxins (Grx) and peroxiredoxins (Prx) belong to the Trx fold superfamily and are able to use reducing equivalents from NADPH via catalytic cysteinyl residues (Cys) to reduce oxidized Cys modifications of specific proteins involved in various cellular processes including immune mechanisms. Interestingly, these proteins can also reduce peroxides and specifically oxidize some of their substrates. Here, we have analyzed protein distribution of representative members of the Trx fold protein family - Trx1, Grx1, Grx2 and Prx2 - in a murine model of allergic asthma bronchiale, as well as their potential therapeutic impact on type-2 driven airway inflammation. Ovalbumin (OVA) sensitization and challenge using the type-2 prone Balb/c mouse strain resulted in increased levels of all investigated proteins in distinct cellular patterns. While concomitant treatment with Grx1 and Prx2 did not show any therapeutic impact on the outcome of the disease, Grx2 or Trx1 treatment before and during the challenge phase displayed pronounced protective effects on the development of allergic airway inflammation. Eosinophil numbers and the type-2 cytokine IL-5 were significantly reduced while lung function parameters profoundly improved. The number of macrophages in the bronchoalveolar lavage (BAL) did not change significantly, however, the harmful release of nitric oxide was successfully prevented by enzymatically active Grx2 ex vivo. Therapeutic activity of Grx2 seems to be dependent on targeting both, disulfides and glutathionylated cysteinyl residues. A mutant lacking the capacity to reduce disulfides showed no protection from airway hyper reactivity and was not able to interfere with macrophage activation, but reduced the number of other immune cells as well as IL-5 release. Altogether, the present study demonstrates that redox-dependent protection against inflammatory damage is based on specific enzyme activities. During OVA-induced allergic airway inflammation Grx2 exerts beneficial and thus potentially therapeutic effects.